1973
DOI: 10.1063/1.1680596
|View full text |Cite
|
Sign up to set email alerts
|

Ionization enhanced diffusion

Abstract: The diffusion equation and diffusion coefficient parametrization are established for the normal ionization-enhanced diffusion mechanism and the Bourgoin mechanism. These mechanisms can facilitate the diffusion of impurities and defects in semiconductors and insulators. The Bourgoin mechanism is athermal, i.e., it does not require thermal activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…As we knew, the phenomenon of ionization enhanced and induced atom migration or diffusion has been observed in ceramics previously [37][38][39][40], another type of mechanism, knock-on damage, may also play a certain role in the high-energy particle irradiation. In our previous similar study in zircon [41], the knock-on collisions induced preferential sputtering of O from surfaces are responsible for the beam damage on zircon in TEM.…”
Section: Resultsmentioning
confidence: 96%
“…As we knew, the phenomenon of ionization enhanced and induced atom migration or diffusion has been observed in ceramics previously [37][38][39][40], another type of mechanism, knock-on damage, may also play a certain role in the high-energy particle irradiation. In our previous similar study in zircon [41], the knock-on collisions induced preferential sputtering of O from surfaces are responsible for the beam damage on zircon in TEM.…”
Section: Resultsmentioning
confidence: 96%
“…The effects of ionization on defect migration rates have been discussed by Bourgoin, Corbett, and Frisch (1973). Changes in migration rates that result because the energy barrier between the lowest energy configuration and the saddle point is difFerent when the defect changes charge state, have been termed ionization enhanced diQus-ion Two other types of ionization effects have also been recognized.…”
Section: At High Temperaturementioning
confidence: 97%
“…Low temperature electron irradiation experiments have long suggested that the self interstitial is mobile in silicon below 4 K [8]. Although these results do not provide a quantitative value of the interstitial diffusivity, they point towards the validity of the Bourgoin-Corbett mechanism of athermal interstitial migration via successive changes in charge state [9]. Ab-initio MD studies by Car et al [ 10] have shown that the equilibrium self-interstitial configuration is the <110> dumbbell, an extended defect which, interestingly, has no states in the gap.…”
mentioning
confidence: 70%